The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/mren.201700059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkyl Aluminums on Ethylene Polymerization Reactions with a Cr‐V Bimetallic Catalyst

Abstract: The effect of introducing various types of alkyl aluminums directly into the catalyst and/or in the polymerization process as cocatalyst on the efficiency of a Cr‐V bimetallic catalyst for ethylene polymerization is systematically investigated. Results indicate that polymerization activity, kinetic behavior, and polymer properties of the Cr‐V catalyst are strongly affected by using alkyl aluminums in different stages of polymerization, due to the different responses and sensitivities of the two metal centers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Generally, the low‐ and the high‐MW peaks are originated from the chromium and vanadium centers in the CrV bimetallic polyethylene catalyst, respectively. [ 32 ] The PDIs of the products by CrV‐1/1‐CA, CrV‐1/2‐CA, and CrV‐1/3‐CA are broader than the counterparts, suggesting that more active sites are involved in the reaction. For CrV‐1/1‐CA and CrV‐1/1 catalysts, the molecular weight of the products are similar as 10.5 × 10 5 g mol −1 , with the PDI obviously changed from 50.1 to 58.2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the low‐ and the high‐MW peaks are originated from the chromium and vanadium centers in the CrV bimetallic polyethylene catalyst, respectively. [ 32 ] The PDIs of the products by CrV‐1/1‐CA, CrV‐1/2‐CA, and CrV‐1/3‐CA are broader than the counterparts, suggesting that more active sites are involved in the reaction. For CrV‐1/1‐CA and CrV‐1/1 catalysts, the molecular weight of the products are similar as 10.5 × 10 5 g mol −1 , with the PDI obviously changed from 50.1 to 58.2.…”
Section: Resultsmentioning
confidence: 99%
“…The final melting curve was carried out on TA DSC Q200 with the authors' previous reported program. [ 31,32 ]…”
Section: Methodsmentioning
confidence: 99%
“…It is well stablished that the first and most important parameter controlling the final polymer properties is the catalyst [5,6]. On the other hand, it is noticed that the nature of this important chemical is practically undeniable without the presence of an activator known as cocatalyst [7,8]. Many advances have been made in the catalysts structural studies and polymerization condition, although the effect of important factors such as electron donor, cocatalyst, and comonomer in the catalyst performance and polymerization process is not very well explored and understood [9].…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Our group utilized the advantages of vanadiumbased catalysts to hybridize different kinds of bimetallic to produce bimodal PE with improved proccessability. [22][23][24][25][26] However, the activities of vanadium-based catalysts were not as high as Ziegler-Natta catalyst. Our group also developed the modified silica-supported vanadium-based catalyst to produce UHMWPE with higher activity compared with the previously published supported vanadium-based catalysts.…”
Section: Introductionmentioning
confidence: 99%